Ideologi Keagamaan, Partai Politik, dan Pendidikan Islam: Refleksi Pemikiran Hasan Al-Banna di Sekolah Islam Terpadu Ukhuwah Banjarmasin - Yunizar Ramadhani (Nalar: Jurnal Peradaban dan Pemikiran Islam)
This study aims to analyze the relationship between Hasan Al-Banna’s thoughts and the practice of Islamic education at Sekolah Islam Terpadu Ukhuwah Banjarmasin. This is a qualitative research by combining literature study and field study and conducted at that Islamic school. The data is collected through observation, interviews and literature study. The analysis reveals that the of Islamic education at Sekolah Islam Terpadu Ukhuwah Banjarmasin not only has a relationship with Hasan Al-Banna’s thoughts, but has an emotional and ideological connectedness to the Muslim Brotherhood and Partai Keadilan Sejahtera (PKS). In addition, the practice of Islamic education at the school has ideological and applicative relevance to Al-Banna’s educational thinking. His thoughts become the ideological foundation of the school and then implemented in its curriculum and educational process. Specifically, the inspiration of the school’s educational practice comes from the Tarbiyah movement of the Muslim Brotherhood. It can be concluded that Sekolah Islam Terpadu Ukhuwah Banjarmasin makes Al-Banna’s religious ideology the foundation of its education, and, furthermore, is the actualization of the Tarbiyah Movement and the media for the educational actualization of Partai Keadilan Sejahtera (PKS).